2020
DOI: 10.1039/d0ce00861c
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility single-crystalline ZnSnN2on ZnO (0001) substrates

Abstract: Making a systematic effort, we have developed a single-crystalline ZnSnN2 on ZnO (0001) by reactive magnetron co-sputtering. Epitaxial growth was achieved at 350°C by co-sputtering from metal targets in nitrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…9 Furthermore, a large absorption coefficient in the range of UV−Vis−NIR is attributed to the ZnSnN 2 material, which makes it competitive with more commonly used photovoltaic materials such as GaAs, CdTe, and InP. 2,7,10 ZnSnN 2 can fulfill the tetrawatt power requirement with its very low cost and environmental compatibility 7 by plentiful and nontoxic materials. 11 Due to these favorable properties, ZnSnN 2 is appealing in terms of both economic and environmental aspects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Furthermore, a large absorption coefficient in the range of UV−Vis−NIR is attributed to the ZnSnN 2 material, which makes it competitive with more commonly used photovoltaic materials such as GaAs, CdTe, and InP. 2,7,10 ZnSnN 2 can fulfill the tetrawatt power requirement with its very low cost and environmental compatibility 7 by plentiful and nontoxic materials. 11 Due to these favorable properties, ZnSnN 2 is appealing in terms of both economic and environmental aspects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 It is a rather undeveloped member of the Zn−IV−N 2 family and the knowledge about ZnSnN 2 is scarce and somewhat contradictory. 2,10,13 The first computational research was reported in 2008. 14 The ZnSnN 2 thin film was first synthesized in 2012, 15,16 and its powder form was first prepared in 2016.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Gogova et al., have reported the growth of single crystalline hexagonal layers at 350 °C by magnetron sputtering on (0002) ZnO substrates providing a lattice mismatch of 4.2%. [ 12 ] Le et al., demonstrated epitaxially grown wurtzite films by plasma‐assisted molecular beam epitaxy (PAMBE) at 450 and 550 °C, using ZnO buffer layers. [ 10 ] Thus, even though the initial demonstrations of the ZnSnN 2 epitaxy have been made, there is a room for explorations.…”
Section: Introductionmentioning
confidence: 99%